Comparative evaluation of the wound-healing potency of recombinant bFGF and ski gene therapy in rats. (3rd July 2016) - Peng, Yan; Li, Ping; Zhao, Zi-Ai; Chen, Lei; Zhao, Xiao-Guang; Chen, Xing; Zhao, Yan; Xiong, Ren-Ping; Ning, Ya-Lei; Yang, Nan; Ye, Jian; Zhou, Yuan-Guo
Abstract: We previously demonstrated that cellular Sloan-Kettering Institute (c-Ski) played a dual role, both promoting wound healing and alleviating scar formation. However, its mechanism and therapeutic effects are not clear, especially compared with widely used treatments, such as basic fibroblast growth factor (bFGF) administration. However, Ski treatment led to an even shorter healing time and a more significant reduction in scar area than bFGF treatment. The mechanism underlying this difference was related to a reduced inflammatory response, more rapid re-epithelialization, less collagen after healing and a greater reduction in the proportion of alpha-smooth muscle actin and SMemb-positive cells after Ski treatment. These results not only confirm that Ski plays a dual role in promoting healing and reducing scarring but also suggest that Ski yields better treatment effects than bFGF, indicating better potential therapeutic effects in wound repair.